European Traditions and the Beginnings of Modern mosaic in Bohemia and Moravia (Theatrum historiae, 2017)
The renovation of the musive technique took place in Venice after the middle of the 19th century. The effort to rescue the mosaics of the local church of San Marco led to the revival of the production of mosaic glass and to the foundation of specialised workshops, which worked on the repairs of earlier works as well as on the creation of new compositions. Generations of mosaicists trained in the Venetian milieu and particularly in the enterprise of Antonio Salviati then spread the specialised activity on the boundary of arts and crafts to other European countries. The personage of Luigi Solerti, who settled in the background of the originally glass painting company of Albert Neuhauser in Innsbruck, is particularly important for Bohemia. The company carried out commissions not only on the territory of Austria but also of all other lands of the monarchy. The operation of foreign mosaicists has been addressed only partially so far within Czech history and art theory. The study offers a new view of the domestic situation, casting light for the first time for a Czech reader on many facts concerning the development of European (particularly Italian and Austrian) mosaic art in the second half of the 19th century.
Keywords: mosaic; restoration; Antonio Salviati (1816-1890); Luigi Solerti (1846–1902); Albert Neuhauser (1832–1901) –; Die Mosaikwerkstätte Albert Neuhauser; Tiroler Glasmalerei- und Mosaikanstalt; Bayerische Mosaikanstalt